The Book that Almost Rhymed - Abed, Omar; Aly, Hatem (New York : Dial Books for Young Readers, 2024)
A boy begrudgingly composes a sometimes-rhyming adventure with his precocious little sister.
Ages 3-7 years.
Keywords: Siblings -- Juvenile fiction; Creative writing -- Juvenile fiction; Cooperativeness in children -- Juvenile fiction; Siblings -- Fiction; Creative writing -- Fiction; Cooperativeness -- Fiction; Stories in rhyme; Picture books